2009
DOI: 10.1104/pp.109.140947
|View full text |Cite
|
Sign up to set email alerts
|

TheREDUCED LEAFLETGenes Encode Key Components of the trans-Acting Small Interfering RNA Pathway and Regulate Compound Leaf and Flower Development inLotus japonicus     

Abstract: The endogenous trans-acting small interfering RNA (ta-siRNA) pathway plays a conserved role in adaxial-abaxial patterning of lateral organs in simple-leafed plant species. However, its function in compound-leafed species is largely unknown. Using the compound-leafed species Lotus japonicus, we identified and characterized two independent mutants, reduced leaflet1 (rel1) and rel3, whose most conspicuous defects in compound leaves are abaxialized leaflets and reduction in leaflet number. Concurrent mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 56 publications
0
55
0
4
Order By: Relevance
“…In Arabidopsis, the juvenile-toadult phase transition is normally suppressed by TAS3a tasiRNAs through the negative regulation of ARF3 mRNA (Fahlgren et al, 2006). Late stages of flower development in Arabidopsis, rice, and Lotus japonicus rely on regulated ARF3 function (Hunter et al, 2006;Liu et al, 2007;Yan et al, 2010). Furthermore, recent data indicate that tasiRNAs are also involved in environmental stress responses (Moldovan et al, 2010).…”
Section: Mirnas/tasirna-arf Responses To Cold Stress In Spikes Of Thementioning
confidence: 99%
“…In Arabidopsis, the juvenile-toadult phase transition is normally suppressed by TAS3a tasiRNAs through the negative regulation of ARF3 mRNA (Fahlgren et al, 2006). Late stages of flower development in Arabidopsis, rice, and Lotus japonicus rely on regulated ARF3 function (Hunter et al, 2006;Liu et al, 2007;Yan et al, 2010). Furthermore, recent data indicate that tasiRNAs are also involved in environmental stress responses (Moldovan et al, 2010).…”
Section: Mirnas/tasirna-arf Responses To Cold Stress In Spikes Of Thementioning
confidence: 99%
“…Tomato (Solanum lycopersicum) WIRY genes are involved in ta-siRNA biogenesis, and the wiry mutants show shoestring leaves with defects in leaf blade expansion (Yifhar et al, 2012). In the legume species Lotus japonicus, mutations in REDUCED LEAFLET1 (REL1) and RE-DUCED LEAFLET3 (REL3), which respectively encode the orthologs of Arabidopsis SGS3 and AGO7, result in abaxialized leaflets with decreased leaflet numbers (Yan et al, 2010). In monocots, more obvious developmental defects have been observed in ta-siRNA pathway-related mutants.…”
Section: Introductionmentioning
confidence: 99%
“…Independent studies have shown that the ta-siRNA pathway is broadly involved in the determination of dorsiventral polarity of leaves among species (Timmermans et al, 1998;Juarez et al, 2004;Liu et al, 2007;Yan et al, 2010). Therefore, the ta-siRNA pathway probably plays a key role in leaf morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the essential role of this pathway in maize and rice development (Nogueira et al, 2007;Nagasaki et al, 2007;Itoh et al, 2008;Dotto et al, 2014), ta-siRNA biogenesis mutants in the eudicots exhibit relatively subtle defects. In Arabidopsis, Medicago, and Lotus, such mutants give rise to downward-curled, lobed, or narrow leaves that are weakly abaxialized (Peragine et al, 2004;Xie et al, 2005;Yan et al, 2010;Zhou et al, 2013). Even in tomato, where ta-siRNA biogenesis mutants show a more severe effect on leaf polarity, these mutants are viable and male fertile (Yifhar et al, 2012;Brooks et al, 2014).…”
Section: Discussion Tasir-arf-directed Regulation Of Arf3 Is Essentiamentioning
confidence: 99%
“…Disruption of this pathway in other eudicot species similarly results in viable plants with partially abaxialized or highly lobed leaves (Yan et al, 2010;Zhou et al, 2013). Even in tomato (Solanum lycopersicum), where the effects of ta-siRNA biogenesis mutants on leaf polarity are more exacerbated, such mutants develop to maturity and remain partially fertile (Yifhar et al, 2012;Brooks et al, 2014).…”
Section: Introductionmentioning
confidence: 99%